2018
DOI: 10.1148/radiol.2017162076
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Early-stage Extracranial Arteriovenous Malformations with Intralesional Interstitial Bleomycin Injection: A Pilot Study

Abstract: Purpose To assess the efficacy and safety of intralesional interstitial bleomycin injection in the treatment of early-stage (Schobinger stage I or II) extracranial arteriovenous malformations (AVMs). Materials and Methods This prospective study involved 34 patients with early-stage AVMs, as defined by the Schobinger staging system. The patients received intralesional interstitial bleomycin injected at a maximum dose of 15 000 IU or 1000 IU per kilogram of body weight for children who weighed less than 15 kg pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…In this case, according to the results of MRI, the patient had the potential for AVM invasion. Precautions such as regular clinical follow-up and bleomycin injection should be taken to prevent AVM formation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, according to the results of MRI, the patient had the potential for AVM invasion. Precautions such as regular clinical follow-up and bleomycin injection should be taken to prevent AVM formation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis provides new management strategies beyond precautions preventing AVM formation and complication with bleomycin injection 18 . Kawasaki et al demonstrated that loss-of-functional mutation in EPHB4 or RASA-1 result in downstream activating of mTORC1, overgrowth of vascular and the development of CM-AVM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, interstitial bleomycin injection has been suggested as a means of down-regulating symptomatic AVMs (Jin et al 2018), though little is yet understood about the mechanism of action of bleomycin in this setting.…”
Section: Arteriovenous Malformationsmentioning
confidence: 99%